Local Governments' Head Election in Indonesia: A Proposal for Asymmetric Model - Ratih Listyana Chandra (Jurnal Kajian Pembaruan Hukum, 2023)
Indonesia has experienced the dynamics of the law on the local governments' head elections. Various mechanisms have been implemented to obtain the ideal model for filling executive positions at the local level. Unfortunately, the government efforts have yet to deliver optimal results. The irregularity of the legal dynamics also eventually caused various Government instability to corruption, post-electoral conflicts, and the high number of disputes over the local election results to the Constitutional Court is evidence of the imperfection of the mechanism adopted by the government. Furthermore, the costs that must be allocated to organize an election are quite high, which is different from the local election results. Moreover, the long process with the tendency of forced candidates produced corrupt and incompetent leaders. Sharing partnerships between the head and deputy of the local government became another problem that is quite a concern in implementing local elections in Indonesia. Thus, this paper examines the ideal model of the head of local government elections in Indonesia. This research focuses on the dynamics of the legislation and regulation on the head of local government elections in Indonesia. The research method applied is normative juridical legal research. The data collection technique employed is the study of documents and literature on secondary data in the form of primary, secondary, and tertiary legal materials. As a result, this study concludes that the ideal model for filling the position of the local head in Indonesia is an asymmetrical– compromise.